1989
DOI: 10.1063/1.101036
|View full text |Cite
|
Sign up to set email alerts
|

Low-temperature selective epitaxial growth of silicon at atmospheric pressure

Abstract: Epitaxial Si has been grown selectively on oxide-patterned substrates from 850 down to 600 °C for the first time in the Si-Cl-H system at atmospheric pressure. Si deposition was achieved by hydrogen reduction of dichlorosilane in an ultraclean system using a load lock. Epitaxy was achieved at low temperatures only when the hydrogen was purified to remove traces of H2O and O2 implying that an oxygen-free environment is the most important factor controlling epitaxy at low temperatures. Cross-sectional transmissi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
36
0

Year Published

1991
1991
2015
2015

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 97 publications
(38 citation statements)
references
References 11 publications
2
36
0
Order By: Relevance
“…Improvements in the quality of gases and equipment have enabled ultraclean low-temperature CVD processing for atomic-order control. [1][2][3][4] Our concept of atomically controlled processing for group IV semiconductors is based on atomic-order surface reaction control by CVD. CVD is one of the film formation methods using chemical reactions on a substrate with reactant source gas and offers many advantages, such as high throughput, in-situ doping, conformal deposition, and selective deposition.…”
Section: Introductionmentioning
confidence: 99%
“…Improvements in the quality of gases and equipment have enabled ultraclean low-temperature CVD processing for atomic-order control. [1][2][3][4] Our concept of atomically controlled processing for group IV semiconductors is based on atomic-order surface reaction control by CVD. CVD is one of the film formation methods using chemical reactions on a substrate with reactant source gas and offers many advantages, such as high throughput, in-situ doping, conformal deposition, and selective deposition.…”
Section: Introductionmentioning
confidence: 99%
“…An ultraclean system equipped with load-lock and hydrogen purifier was used by T. 0. Sedgweck et al [3] to selectively deposit epitaxial silicon using DCS/Hz at atmospheric pressure. J. L. Regolini et al [4] have demonstrated that the selective epitaxial growth of silicon can be achieved at reduced pressure of 2 ton…”
Section: Introductionmentioning
confidence: 99%
“…The four net reactions are part of a growth-etch model characterizing the nature of the Si surface and oxide under various processing conditions. Several low-temperature epitaxial growth techniques, such as UHV/CVD (17) and atmospheric pressure chemical vapor deposition (26) have been successfully demonstrated based on operation in a region of the growth-etch model that allows for an oxide-free surface. The most important factor is the reduction of O2 and H20 partial pressures.…”
Section: In Situ Cleaningmentioning
confidence: 99%
“…Low-temperature CVD techniques such as ultrahigh vacuum CVD (UHV/ CVD) (17), plasma-enhanced CVD (PECVD) (18)(19)(20)(21)(22), remote plasma CVD (RPCVD) (23)(24), and photo-induced epitaxy (25) have also been studied. Recently, Sedgwick et al have lowered epitaxial growth temperatures down to 600~ at atmospheric pressure by using purified hydrogen (26).…”
mentioning
confidence: 99%